"Nature's Marvels": The Value of Collections Extracted from Colonial Western Australia. Issue 2 (3rd April 2021) - Paterson, Alistair; Witcomb, Andrea
ABSTRACT: The history of collecting in Western Australia demonstrates some unique as well as exemplary features that we suggest can illuminate aspects of collecting more broadly. This article seeks to contribute to scholarship on the history of collecting by arguing for the importance of understanding the ways in which the value of collections—to collectors, institutions and knowledge producers—has been produced. We call this focus on value an extractive value-adding approach to collection studies. Deploying this approach reveals not only the close relationship between collecting practices and colonialism, but also the ways in which types of values are made, not given, and the processes involved in their production. By revealing the social context of these processes, our hope is that new understandings of these collections can be produced—that address the colonial legacies embedded in the making of these collections and the purposes to which they were put at the time of their making. This focus is uniquely relevant to Australian studies because the integration of collection studies across natural and ethnographic domains, economics, history and cultural theory is able to clearly interrogate the relationship between collecting practices and colonisation in Australia.